2004
DOI: 10.1002/bit.20184
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, optimization, and structures of cross‐linked enzyme aggregates (CLEAs)

Abstract: The broad applicability of the cross-linking of enzyme aggregates to the effective immobilisation of enzymes is demonstrated and the influence of many parameters on the properties of the resulting CLEAs is determined. The relative simplicity of the operation ideally lends itself to high-throughput methodologies. The aggregation method was improved up to 100% activity yield for any enzyme. For the first time, the physical structures of CLEAs are elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
314
0
17

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(356 citation statements)
references
References 20 publications
16
314
0
17
Order By: Relevance
“…A β-gal imobilizada por CLEA foi reportada em várias obras da literatura (Schoevaart et al, 2004;Gaur et al, 2006;Sheldon, 2010;Li et al, 2015). Contudo, não foi avaliada a β-gal de K. lactis ou a adição de uma proteína espaçadora durante a imobilização, visando a diminuição da resistência à transferência de massa e o entrecruzamento excessivo.…”
Section: Ufscar -São Carlos -Sp 16 a 19 De Julho De 2017unclassified
“…A β-gal imobilizada por CLEA foi reportada em várias obras da literatura (Schoevaart et al, 2004;Gaur et al, 2006;Sheldon, 2010;Li et al, 2015). Contudo, não foi avaliada a β-gal de K. lactis ou a adição de uma proteína espaçadora durante a imobilização, visando a diminuição da resistência à transferência de massa e o entrecruzamento excessivo.…”
Section: Ufscar -São Carlos -Sp 16 a 19 De Julho De 2017unclassified
“…On the other hand, glycosylated enzymes ss-Galactosidase formed "well dispersible suspensions" which showed no difference in activities when assayed by two different fast and slow assays [42]. The issue of cluster size and nature of enzyme molecule had been studied at a greater length by the same group [49]. Majumder et al, (2008) [24] showed that extent of crosslinking also affected cluster size and same enzyme can give CLEA clusters of different morphology and size.…”
Section: Crosslinked Enzyme Aggregates (Clea)mentioning
confidence: 99%
“…[10][11][12][13][14][15] In spite of these attempts, a standard process for GOx immobilization has not yet been developed. Furthermore, GOx immobilization research to date has mostly focused on only increasing the amount of immobilized GOx without serious consideration of how to improve the electron transfer between the immobilized GOx molecules and supporter materials.…”
Section: Introductionmentioning
confidence: 99%